El mtodo heurstico de Polya para mejorar capacidad de resolucin de problemas en el rea Matemtica de Educacin Secundaria - Laguna Estrada, Frank Robert (2019)
The study aims to determine that the use of the Polya Heuristic method significantly improves the ability to solve mathematical problems. For which the heuristic method was applied through a quasi-experimental design, in which 53 second-year secondary school students of the Emblematic Educational Institution San Juan participated. The one that was divided into two working groups: 25 students belonged to the control group and 28 students were part of the experimental group. Likewise, a qualified test divided into four dimensions was used as a data collection instrument: to understand the problem, plan the strategy, execute the strategy and reflect on the strategy used, both for the pre-test and for the post-test. The results show that there is a significant improvement between the pre test and the post test._x000D_ Therefore, we can conclude that the use of the Polya Heuristic method significantly improves the development of problem solving capacity in the area of mathematics.